Perlindungan Hukum Bagi Pencipta Gambar Livery Bus Yang Digunakan Dalam Mode Game Bus - Achmad Mudzakky Al Faruq (Journal of Private and Economic Law, 2021)
ABSTRACT: The image of the bus livery is a characteristic that is owned by bus companies in Indonesia, with the differences in each existing bus, the public can recognize it easily. However, many parties deliberately use this livery bus image without permission from the original creator or copyright holder by using it in the game bus mode, there are even certain parties who are trying to benefit by adjusting the livery bus image through existing social media. This study uses a normative research method with a statutory and conceptual approach. The results showed that legal protection for the creator of the livery bus image used in the bus game mode according to M. Isnaeni's opinion is external and internal. The regulation regarding the protection of works in the form of livery bus images is regulated in Undang-Undang Number 28/2014 about Copyright, which regulates several important points, namely the economic rights of the creators and copyright holders, copyright limitations, types of actions that are not considered copyright infringements, the copyright protection divided into 2, namely protection of moral rights and economic rights. The consequences for bus game mode business actors who use the livery bus image without rights are in the form of claim for compentation in the Copyright Law, and monitor close and even block media accounts of business actors because they have committed copyright infringement by selling and buying images. The livery bus is in bus game mode, the creator can prevent it by giving a license to the work or registering it with the Director General of IPR. efforts to resolve disputes between creators and copyright actors can be carried out in 3 ways, namely mediation, arbitration or court (litigation).